ONOMATOPE BENTURAN PADA SHOUNEN MANGA JEPANG DALAM KOMIK KIMETSU NO YAIBA VOL 1-3 - Imawan Saputra; Yenny Aristia Nasution; Arza Aibonotika (Undiksha Press, 2022)
Onomatopoeia is the designation for sound replicas. The study was intended to describe the characteristics of onomatopoeia and their meanings found in comics. The study focused on onomatopoeia types that showed the sound of inanimate objects, particularly collisions. The thumping group may be grouped into 8, which is 1) blows, shots, and kicks 2) strikes, 3) slaps, 4) slaps, 5) slaps, 6) crashes of objects with hard objects, 7) crashes of objects falling, and 8) objects suddenly collide. Data in this study is the thump taken from the comic kimetsu no yaiba vol 1-3. The theory used in this study is onomatope theory according to Akimoto (2002). Analysis of 51 data shows that there are 7 types of collisions in the comic Kimetsu no Yaiba vol 1-3. Onomatope found in the comic book is primarily 'loud and heavy' and 'sudden occurrences’.